Re-articulating the Third World coalition : the role of the environmental agenda. - WILLIAMS, Marc (1993)
Examines the origins, key institutional features and major factors affecting the development of the Third World coalition. Discusses the evolution of a Third World perspective on environmental problems and examines the interests of Third World countries in the negotiations on global environmental change. Assesses the likely impact of negotiations on global environmental change on the Third World coalition.